Republic of Yemen : 2014 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility-Staff Report; Press Release; and Statement by the Executive Director for the Republic of Yemen. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
KEY ISSUES Background: Yemen has made good progress since the 2011 crisis in advancing the political transition. However, the fledgling economic recovery remained insufficient to make a dent in unemployment and poverty, and fundamental reforms were postponed for fear of derailing the National Dialogue that was central to the political transition. The macroeconomic situation weakened further since early 2014, with increased sabotage of oil facilities leading to a decline in oil revenue and, therefore, a deterioration in the fiscal and external positions and severe fuel and electricity shortages. To address the difficult economic situation, the authorities have adopted a bold reform agenda to preserve macroeconomic stability and set the stage for boosting growth, employment creation, and poverty alleviation. They requested Fund support under an ECF arrangement with access of 150 percent of quota in consideration of the strength of the reforms and large financing needs. Outlook and Risks: Growth and other macroeconomic indicators are projected to improve steadily over the medium term as a result of the reform efforts and improvements in security. Institutional capacity constraints and/or deterioration in security or the political environment could delay reform implementation, in particular energy subsidy reforms. Such delays could destabilize the economy and necessitate even stronger adjustments later on. Policy Discussions: Discussions focused mainly on sequencing and speed of reforms in view of the large financing needs of the budget. Since the successful implementation of the RCF in 2012, there has been an ongoing dialogue with the authorities and a broad agreement on priority reforms, with differences of views on the timing and feasibility of the various reforms during the political transition. After the recent progress achieved in advancing political transition, and the increased economic challenges, the authorities have decided to move ahead with a strong reform program. The program aims to reduce the fiscal deficit to more manageable levels and reorient public spending from generalized subsidies to infrastructure investment and direct social transfers, with the objective to generate growth and employment and better benefit the poor. The authorities also agreed with staff on the need to improve fiscal performance by eliminating ghost workers and double dippers from the civil service payroll, and by increasing nonhydrocarbon revenue. Other agreed reforms aim at ensuring financial sector soundness and improving intermediation and the business environment to support growth and job creation. Other Article IV Issues: An updated debt sustainability analysis indicates that the risk of debt distress continues to be moderate. Plans to introduce fiscal federalism need to ensure appropriate expenditure and debt-contracting policies and controls. A gradual increase in exchange rate flexibility over the medium term would help protect competitiveness and reserves, and would support growth and job creation. More efforts are needed to further improve economic data and to strengthen capacity in AML/CFT.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet